Neurodevelopment and Cognitive Impairment in Parents and Progeny of Perinatal Dietary Protein Deficiency Models - Abey, Nosarieme O.; Ebuehi, Osaretin A. T.; Imaga, Ngozi O. A. (Frontiers in Neuroscience, 2019)
Development of the human conceptus absolutely depends on adequate and balanced supplies of key nutrients; therefore, an important element of neurodevelopmental process is improved nutritional status especially at the critical period of development, perinatal age. This study sought to investigate the effect of maternal protein deficiency during gestation (F0) and lactation on neurological functions of subsequent (F1 and F2) generations, establishing the possible consequential mechanistic association. Rats in four groups were fed different ration of protein diet (PD) as formulated; 21% PD, 10%PD, 5%PD and control diet (rat chow), from adolescent through to gestation and Lactation, and next generations were weaned to the maternal diet group. Neurobehavioral studies (which include; Surface righting reflex, Negative geotaxis, Learning and Memory tests), Brain oxidative stress and Quantification of Serotonin and Dopamine level in the brain. Result shows significant altered neurobehavior reflected in the reduction in reflex response and negative geotaxis score at P≤ 0.05. There was also a transgenerational cognitive impairment in the F1 generation, following perinatal protein malnutrition. The Y-maze (Spatial memory: 5%PD; 8.3%, 10%PD; 9.25% 21%PD; 57.6% and control 55.95%), Morris water Maze (cognition: 5%: 26.5s; 10%;21s, 21%;5s and control; 6s, as escape latency time). The significant increase in dopamine level, decrease in the antioxidant capacity of the protein deficient F1 brain is consistent with the decrease in the brain serotonin concentration (Control;7±0.2, 21%PD; 7.8±0.9 compared to 10%PD; 2.9±0.3 and 5%PD; 2.7±0.3) that is important to neurodevelopment and function. Therefore, persistent early life protein deficiency mediates dysfunction in neurodevelopment and this involves life-long changes in key neurotransmitters and the brain redox status underlying the neurobehavioral display.